Tinjauan Dampak Artificial Intelligence terhadap Mahasiswa Hukum dan Urgensi Pembentukan Regulasi Penggunaannya - Azzahra Nurintiara (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The development of Artificial Intelligence (AI) has brought significant transformations across various sectors, including legal education. Law students, as future legal professionals, must understand both the opportunities and challenges posed by AI. Nowadays, there is no comprehensive regulation governing the use of AI in legal education, raising concerns abour legal gaps, academic intregrity, and graduate competency. This study aims to analyze the impact of AI on law students and highlight the urgency of establishing regulatory frameworks for its use. The research employs a qualitative method with a normative juridical approach. The findings indicate that while AI can enhance the productivity of law students, it also has the potential to erode critical thinking skills and endanger students’ personal data if misused. Therefore, regulations are needed to define clear boundaries for AI use, ensure source transparency, and strengthen legal education curricula to adapt to technological advancements.